Wie wirken gemeldete SPS-Maßnahmen? Ein Gravitationsmodell des Rindfleischhandels der EU - Marc Kramb; Roland Herrmann (Justus-Liebig-Universität Gießen, Zentrum für Internationale Entwicklungs- und Umweltforschung (ZEU), 2009)
For decades, nontariff trade barriers (NTBs) have been regarded as more problematic policy instruments than tariffs in international trade negotiations. This is due to the fact that trade impacts of nontariff trade barriers are less transparent than those of tariffs. Tariffication of nontariff agricultural trade barriers was finally decided under the Uruguay Round of GATT. Although the OECD concluded that a reduction of NTBs took place after 1994, this finding can be challenged. First, tariff-rate quotas (TRQs) are not counted as NTBs by law although they cause effects similar to those of quotas. The number of TRQs has increased strongly after the Uruguay Round. Second, sanitary and phytosanitary measures, i.e. SPS measures, have become more important as notifications under the SPS Agreement do show. There are only few empirical studies available which analyze the effects of these SPS measures. WTO Notifications under the SPS Agreement are utilized in this contribution for measuring trade impacts of sanitary and phytosanitary trade barriers. We explain the WTO data base on SPS notifications. Then, a gravitation model is applied to the EU beef trade in the period January 1995 to June 2001. It is investigated how SPS measures, introduced by non-EU countries in the context of BSE, affected bilateral trade with the EU. We distinguish between 31 product groups which might be affected, and a fixed-effects model is used for analyzing the panel data. We elaborate that SPS measures related to BSE reduced EU beef export revenues in the major product categories significantly. The NTBs did not reduce exports to zero, however, as might have been expected. The percentage reduction of export revenues was 49 % for live cattle, 74 % for fresh and cooled beef and 86 % for frozen beef. For most other product groups, the percentage decline in sales was significant but lower in percentage terms. Apparently, SPS notifications indicate that bilateral trade is restricted but it does not definitely show that the notified measures by the importing country are actually implemented and for which time period. It seems very important in future analyses of the SPS measures to distinguish carefully between SPS notifications and SPS measures.
Keywords: 330; SPS measures; SPS notifications; gravitation model; EU beef exports; bovine spongiform encephalopathy; WTO; nontariff trade barriers; Rindfleisch; Exportbeschränkung; Tierkrankheit; WTO-Regeln; Nichttarifäre Handelshemmnisse; Gravitationsmodell; EU-Staaten; Welt